Comparing Cash and Voucher Transfers in a Humanitarian Context : Evidence from the Democratic Republic of Congo - Aker, Jenny C. (World Bank, Washington, DC, 2015)
Despite recent calls in support of cash transfers, there is little rigorous evidence of the relative impacts of cash versus in-kind transfers, especially in humanitarian contexts, where a majority of such programs take place. This paper uses data from a randomized experiment in the Democratic Republic of Congo to assess the relative impacts and costs of equivalently valued cash and voucher transfers. The voucher program distorted households’ purchases along both the extensive and intensive margin as compared with unconstrained cash households. Yet there were no differences in food consumption or other measures of well-being, in part due to the fact that voucher households were able to resell part of what they purchased. As there were no significant benefits to vouchers, cash transfers were the more cost effective modality for both the implementing agency and program recipients in this context.